Development of a Qur’an Memorization Method with 3T for Male Students at the Rumah Qur'an Blumbang, Purbalingga - Rizky, M. Azidan; Nurrohim, Ahmad; Amanu, Masykur; Marzuqi, Ammar Zain (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Memorizing the Qur'an is a very noble worship and has many virtues. In the matter of memorizing the Qur’an there are many methods taught by teachers to their students that are used to achieve the goal of memorizing the Qur’an. Of the several existing methods, each method must have advantages, characteristics, and disadvantages. There are several phenomena among parents, especially fathers, who have difficulty finding methods that make it easier for them to memorize the Qur’an. 3T is a memorization method with Tasmi', Tafahhum, and Tikror. The object of this research is the students of the Blumbang Qur'an House, Purbalingga. This research is field research with a qualitative descriptive method, carried out through observation, interviews, and documentation studies. The objectives of this study are: 1) To describe the application of the 3T method. 2) To measure the effectiveness of applying the 3T method. 3) To find out the results of the achievement of the application of this method. 4) To find out the factors that hinder and support the application of this method.